2013
DOI: 10.1111/pin.12115
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of regional neutrophil apoptosis promotion by ribosomal protein S19 oligomers in resolution of experimental acute inflammation

Abstract: Isolated peripheral neutrophils spontaneously underwent apoptosis in association with extra-cellular liberation of the monocyte-attracting ribosomal protein S19 (RP S19) oligomers. This apoptosis was prevented by the simultaneous presence of anti-RP S19 antibodies or of a C5a receptor antagonist, but was promoted by supplementing extrinsic RP S19 oligomers. Transformed HL-60 cells to overproduce Gln137Asn-mutant RP S19 were differentiated to neutrophil-like cells. The neutrophil-like cells gained resistance ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…So far, most ribosomal proteins have been identified to bind to certain regions of ribosomal RNA and perform catalytic functions. Many ribosomal proteins have various extra-ribosomal functions, such as DNA repair, transformation, development, apoptosis, and transcription ( Lee et al, 2010 ; Nishiura et al, 2013 ; Nosrati, Kapoor & Kumar, 2014 ). Some studies show that these proteins may play a role in human tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most ribosomal proteins have been identified to bind to certain regions of ribosomal RNA and perform catalytic functions. Many ribosomal proteins have various extra-ribosomal functions, such as DNA repair, transformation, development, apoptosis, and transcription ( Lee et al, 2010 ; Nishiura et al, 2013 ; Nosrati, Kapoor & Kumar, 2014 ). Some studies show that these proteins may play a role in human tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The RP S19 polymer does not induce a C5aR-mediated downstream signal but stimulates RGS3 expression via the C5aR on neutrophils (Nishiura et al, , 2009(Nishiura et al, , 2010a. Therefore, we suggested that RGS3 expression via de novo-synthesized C5aR on neutrophils participates in the shortening of the cell lifespan (Nishiura, 2013;Nishiura et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Neutrophils, the most numerous immune cells in the first line of protection against invading microbes, are characterized by a very short lifespan ( 27 ); their normally short lifespan in the circulation can be manipulated and extended at sites of inflammation, to ensure that an appropriate host response is mounted in response to infection or tissue injury. However, uncontrolled neutrophil recruitment or inappropriate neutrophil longevity is pathophysiologically involved in the development of inflammatory diseases with unresolved neutrophilic inflammation ( 28 ). For instance, a delay in apoptosis may lead to the prolonged release of neutrophil products and direct tissue injury, thus participating in the development of ARDS ( 10 ).…”
Section: Discussionmentioning
confidence: 99%